2004
DOI: 10.1095/biolreprod.104.031112
|View full text |Cite
|
Sign up to set email alerts
|

Two Isoforms of the Leptin Receptor Are Enhanced in Pregnancy-Specific Tissues and Soluble Leptin Receptor Is Enhanced in Maternal Serum with Advancing Gestation in the Baboon1

Abstract: Leptin is a polypeptide hormone produced by adipose and other endocrine tissues. Although it has been linked to receptor-mediated pathways that directly influence human conceptus development, mechanisms that regulate the leptin receptor in pregnancy-specific tissues remain unclear. Therefore, we assessed leptin-receptor ontogeny and regulation in the baboon (Papio sp.), a primate model for human pregnancy. Placentae, decidua, and amniochorion were collected from baboons in early (Days 54-63, n = 4), mid (Days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Second, our data concerned only the end of pregnancy; leptin receptors have been found to be regulated and to change under certain circumstances such as pregnancy. In several species, the expression of multiple forms of the leptin receptor switch in placenta during the course of pregnancy (Edwards et al, 2004;Smolinska et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our data concerned only the end of pregnancy; leptin receptors have been found to be regulated and to change under certain circumstances such as pregnancy. In several species, the expression of multiple forms of the leptin receptor switch in placenta during the course of pregnancy (Edwards et al, 2004;Smolinska et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This difference might have resulted from the sampling frequency in the present study, with 10-day intervals from November 17 to February 15, while just 17 blood samples from March to November were used in the previous study. Although we cannot describe the definite mechanism of the drastic elevation in the serum lepin concentration, one possibility is that recently discovered soluble LRs and previously identified long-and short-form LRs might modulate leptin abundance, as reported in baboons [6]. This significant and drastic increase in the serum leptin concentration may indicate that leptin plays roles as a physiological signal at this time (late November) in Japanese black bears.…”
mentioning
confidence: 78%
“…These studies have demonstrated that there are correlated seasonal changes in blood leptin concentration and body mass in the woodchuck and brown bear and that there was no correlation between the leptin concentration and BMI, body mass or body fat mass in the raccoon dog and blue fox. Recently it has been known that leptin does not always function reduction of body weight because pregnant women exhibit high blood level of leptin during gestation and require more energy without food intake reducing [9], and that soluble leptin receptors (LRs) in blood but not longform and short-form LRs modulate circulating leptin levels in baboons and rats [6,12]. It has also been reported that leptin might play some roles in reproductive events, such as puberty [4], oocyst maturation and early embryonic development [2,3,15] and implantation [18,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because this sex difference emerged only after puberty it may reflect the action of sex steroids, with testosterone stimulating and/or ovarian steroids inhibiting tissue expression of Ob-Re. Estrogen appears to suppress Ob-Rb expression in the rat choroid plexus, hypothalamus (Bennett et al 1999) and ovary (Duggal et al 2002), although in the baboon placenta estrogen suppression induced by fetectomy was recently shown to reduce placental expression of the long form of Ob-R (Edwards et al 2004). Interestingly, a putative estrogen response element has been identified on the Ob-R promoter in the rat (Lindell et al 2001), but it remains unclear how this might influence tissue expression of the specific Ob-R isoforms, including Ob-Re.…”
Section: Discussionmentioning
confidence: 99%